What does Neural Plasticity Tell us about Role of Primary Visual Cortex (V1) in Visual Awareness? - Silvanto, Juha; Rees, Geraint (Frontiers in Psychology, 2011)
The complete loss of visual awareness resulting from a lesion to the primary visual cortex (V1) suggests that this region is indispensable for conscious visual perception. There are however a number cases of conscious perception in the absence of V1 which appear to challenge this conclusion. These include reports of patients with bilateral V1 lesions sustained at an early age whose conscious vision has spontaneously recovered, as well as stroke patients who have recovered some conscious vision with the help of rehabilitation programs. In addition, the phenomenon of hemianopic completion and percepts induced by brain stimulation suggest that V1 may not be necessary for conscious perception in all circumstances. Furthermore, that the visual abilities in the cat are associated with the recovery of normal extrastriate tuning properties rather than emulation of V1 functions suggests that there is nothing unique about the functional properties of this region in visual awareness. Rather, the dramatic effect of a V1 lesion on visual awareness may be due to its role in providing the majority of extrastriate visual input, the loss of which abolishes normal neural responsiveness throughout the visual cortex.